Helianthus tuberosus and polyamine research: Past and recent applications of a classical growth model - Tassoni, Annalisa (2010)
The earliest studies concerning polyamines (PAs) in plants were performed by using in vitro cultured explants of Helianthus tuberosus dormant tuber. This parenchyma tissue was particularly useful due to its susceptibility to several growth substances, including PAs. During tuber dormancy, PA levels are too low to sustain cell division; thus Helianthus represents a natural PA-deficient model. When cultivated in vitro in the presence of auxins, Helianthus tuber dormant parenchyma cells at the G(0) stage start to divide synchronously acquiring meristematic characteristics. The requirement for auxins to induce cell division can be substituted by aliphatic PAs such as putrescine, spermidine or spermine. Cylinders or slices of explanted homogeneous tuber parenchyma were cultured in liquid medium for short-term studies on the cell cycle, or on solid agar medium for long-term experiments. Morphological and physiological modifications of synchronously dividing cells were studied during the different phases of the cell cycle in relation to PAs biosynthesis and oxidation. Long-term experiments led to the identification of the PAs as plant growth regulators, as the sole nitrogen source, as tuber storage substances and as essential factors for morphogenetic processes and cell homeostasis. More recently this system was used to study the effects on plant cell proliferation of platinum- or palladium-derived drugs (cisplatin and platinum or palladium bi-substituted spermine) that are used in human cancer cell lines as antiproliferative and cytotoxic agents. Cisplatin was the most active both in cell proliferation inhibition and on PA metabolism. Similar experiments were performed using three agmatine analogous. Different effects of these compounds were observed on cell proliferation, free PA levels and enzyme activities, leading to a hypothesis of a correlation between their chemical structure and the agmatine metabolism in plants.